California Elected Women's Association for Education and Research membership letter - Sue Hone:::::: (1977)
This 1977 membership letter from the California Elected Women's Association for Education and Research (CEWAER), signed by President Sue Hone, highlights the organization's network of women leaders—including judges, mayors, councilmembers, supervisors, and a congresswoman—and outlines benefits for members. These include newsletters, a member directory, conferences, a resume bank, research support, regional organizing assistance, and professional networking. The letter encourages women to join or renew their membership, noting annual dues of $15.